Pesem "Teorija strun" Richarda Jacksona in interpretacija poezije kot nezavednega stroja - Osojnik, Iztok (Primerjalna književnost, 2019)
The poem "String Theory" by Richard Jackson first addresses the relationship between poetry and its interpretation (theory, physics, psychoanalysis or even philosophy). I introduce a few concepts focusing on "the stain" of the poem, caused by futility of searching for the meaning of the poem and its interpretation. Notions of its inner timeness and of the unconscious will be introduced to reach beyond the conventional interpretation. How does a poem happen? When does it happen? The interpretative actualization of the poem should eradicate any particular individuality. What goes for unconscious in the Lacanian psychoanalysis goes for poetry too: unconscious workings are in the form of deformation, not in the content. So whatever subjectivity (the lyrical subject) still persists in the poem it always directs one's attention to such deformation, a stain, a scream in the poem. How does this stain articulate itself so that it is a poem (of futile love, melancholy) but not e.g. theory of physics, nor any mystic contemplation of the divine light? The String Theory poem vibrates between fragmented dreams as subconscious language that enables the satisfaction of the unconscious and suppressed "stained" memory, the traumatic nucleus, that keeps running the recurrence of the uncomfortable feelings and distress. Hopefully my interpretative reference to the poem The String Theory could provoke the appearance of the existential Thing that will offer itself to us as a present by unbearably evading us and that is exactly what we ascribe to the function of poetical discursivity.
Keywords: ameriška književnost; ameriška poezija; fenomenologija; Jackson, Richard; literarna interpretacija; psihoanaliza